Effects of different types of written vaccination information on COVID-19 vaccine hesitancy in the UK (OCEANS-III): a single-blind, parallel-group, randomised controlled trial - Freeman, D; Loe, BS; Yu, L-M; Freeman, J; Chadwick, A; Vaccari, C; Shanyinde, M; Harris, V; Waite, F; Rosebrock, L; Petit, A; Vanderslott, S; et al. (Elsevier, 2021)
Background The effectiveness of the COVID-19 vaccination programme depends on mass participation: the greater the number of people vaccinated, the less risk to the population. Concise, persuasive messaging is crucial, particularly given substantial levels of vaccine hesitancy in the UK. Our aim was to test which types of written information about COVID-19 vaccination, in addition to a statement of efficacy and safety, might increase vaccine acceptance.